2013
DOI: 10.4161/cc.23511
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction mechanisms of a p53 peptide and nutlin with the MDM2 and MDMX proteins: A Brownian dynamics study

Abstract: Inhibition of this interaction has become an important therapeutic strategy in oncology. Although MDM2 and MDMX share a very high degree of sequence/ structural similarity, the small-molecule inhibitor nutlin appears to be an efficient inhibitor only of the p53-MDM2 interaction. Here, we investigate the mechanism of interaction of nutlin with these two proteins and contrast it with that of p53 using Brownian dynamics simulations. In contrast to earlier attempts to examine the bound states of the partners, here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 75 publications
1
39
0
Order By: Relevance
“…Inspection of the radial residence time profiles of the p53-based peptide mutants, (Figure 1a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 34,48 . Interestingly, the encounter complex configurations corresponding to the dominant basins of attractions of the phage-derived peptide series (Figure 2d) reveal that the peptides approach MDM2 through their N-terminal ends.…”
Section: Effect Of Qetfsdlwkllp C-terminal Substitution On Peptide Rementioning
confidence: 94%
“…Inspection of the radial residence time profiles of the p53-based peptide mutants, (Figure 1a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 34,48 . Interestingly, the encounter complex configurations corresponding to the dominant basins of attractions of the phage-derived peptide series (Figure 2d) reveal that the peptides approach MDM2 through their N-terminal ends.…”
Section: Effect Of Qetfsdlwkllp C-terminal Substitution On Peptide Rementioning
confidence: 94%
“…Hence, the present study focuses on identifying the feasibility of HIV IN dimerization via both core and reaching dimer interfaces using Brownian dynamics simulations. The application of Brownian dynamics in calculating the association or dissociation rate constant in protein complex is well reported (Gabdoulline & Wade 1998; Elsawy et al 2010; Mereghetti, Kokh, McCammon & Wade 2011; Pang, Qin & Zhou 2011; ElSawy et al 2013). In Brownian dynamics, the formation of an encounter complex is generally assessed by any one of the parameters such as buried surface area threshold, RMSD threshold, energy criteria or residue contact criteria (Janin 1997; Gabdoulline & Wade 1998; Vijayakumar et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, structural and energetic insights into the complex formation pathway of several multimeric proteins have been elucidated successfully by molecular dynamics simulations (Gilson & Zhou 2007; Stoica, Sadiq & Coveney 2008; Hou, Wang, Li & Wang 2010; Hu, Wang, Liu & Zhang 2010; Rastelli, Del Rio, Degliesposti & Sgobba 2010; Hu, Zhang & Chen 2011; Sangeetha, Muthukumaran & Amutha 2015). In recent years, protein-protein interaction kinetics and the elucidation of association/dissociation rates have been investigated by computational methods, due to various limitations in experimental procedures such as the limited accessible rates (difficult for reactions faster than ~10 6 M −1 s −1 ) and occurrence of multiple short living transition states (Gabdoulline & Wade 1997; Spaar, Flock & Helms 2009; Elsawy, Caves & Twarock 2010; ElSawy et al 2013). Brownian dynamics (BD) simulations are used widely to calculate the rate of protein-protein associations and a reaction is considered as a fast reaction, when the rate of association is greater than 10 6 M −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…3; left). In previous work, 36,37 we showed that the interaction landscape of wild-type p53 with MDM2 ( Fig. 3a; left) is characterized by broad basins of attraction, with the 2 highest occupied basins, basins 1 and 2, lying close to the C-and N-terminal regions of the MDM2 protein surface respectively, away from the binding site, and a third basin of attraction, basin 3, lying further away from the MDM2 surface.…”
Section: Interaction Landscape Of Phosphorylated P53 With the Mdm2 Prmentioning
confidence: 99%
“…[31][32][33][34][35][36] In previous work, [36][37][38] we showed, through Brownian dynamics analysis, that the residence time of the drug receptor encounter complex is an alternative and effective means for explaining the preferential binding of Nutlin and p53 to MDM2 36,37 and for understanding the dynamic determinants for the differential binding of Nutlin geometric isomers to MDM2. 38 In this work, we extend this approach to study the effect of p53-peptide phosphorylation on the dynamics of its interactions with the N-terminal domain of MDM2 (residues 25-109).…”
Section: Introductionmentioning
confidence: 99%